Murottal Therapy in Schizophrenia Patients with Nursing Problems of Violent Behavior - Yunianti, Evita; Oktaviana, Wita; Yanto, Tri Wahyudi (PT Saintek Medika Nusantara, 2023)
Mental disorders are behavioral patterns that are usually accompanied by symptoms of limitations or disorders in one or more of the main human functions, such as psychological, behavioral, biological, or disruptive functions that involve interaction with others or with the community. This study is a case report with a nursing care management approach that includes assessment, data analysis, formulating nursing diagnoses, interventions, implementation and then evaluation. This family nursing care is provided based on Evidence-based Nursing Practice after determining the diagnosis based on the assessment data, then the intervention is prepared by reviewing several literatures that report on murottal therapy for clients at risk of violent behavior. The results of the literature review are then applied to nursing care. The collection of nursing care data was carried out using an assessment form and interviews. After murottal therapy was carried out 3 times within a period of 3 days, before the intervention, Mr. M had a threshold score of 5. The higher the threshold score, the more the anger level peaks and is uncontrollable. After murottal therapy, the anger threshold score was 1. The results of the application of murottal therapy in nursing care with patients who have a risk of violent behavior show that murottal therapy can have an impact or increase anger control.